Paciente femenina de 73 años de edad con tromboembolismo pulmonar. - Ramos Mosquera, Samantha Valentina (2021)
Pulmonary thromboembolism is also called pulmonary embolism, this happens when there is a detachment of a thrombus that is in an artery or vein and it travels and adheres in pulmonary arteries, it is highly fatal, when it is not diagnosed in time, this in largely because it is a stealthy disease and sometimes difficult to diagnose. Pulmonary thromboembolism can attack anyone, but there are risk factors that increase the risk, such as previous surgeries, people with poor circulation, extended immobilization, among others. The most used treatment is the anticoagulant, as long as there is no type of contraindication, the correct use influences its efficacy in the short or long term. Complementary tests are essential for the use of the correct therapy, the goal of treatment is to avoid recurrent thromboembolism and or its expansion.